Modelagem do crescimento e da produção florestal em povoamentos de eucalipto desbastado e não desbastado - Silva, Gabriela Cristina Costa (2017)
Techniques that provide information about the site quality and the prediction of growth and yield are essential for forest management. This estimate is obtained through the growth and yield models, fundamental for forest planning. Therefore, the use of models with adequate functional relationship and flexibility results in modeling efficiency. Demands for logs of greater diameter and quality require the use of management methods that lead to faster cycles and that promote greater increment, reducing the pressure on the native forests and adding more value to the final product. Thus, thinning and pruning are techniques that allow wood to be obtained with these characteristics. In this context, the objective of this work was to perform the classification of the site quality stands, from which, the Clutter system of equations (1963) were fitted, seeking the most adequate form of volumetric model to estimate the growth and yield of Eucalyptus plantations, submitted and not submitted to thinning. The site quality was performed by the guide curve method for the two databases, and an analysis of the longitudinal trajectory data in the unthinned database was made. The selection of the Clutter model was performed by two-stage adjustment of 57 possible functional relationships and the analysis of the model modified from the interpretation of the parameters to select the most suitable volumetric model form. The Chapman-Richards model was the one that best fit the two databases for the classification of productive capacity, and the thinning down does not affect the growth in dominant height. Using the selected Clutter (1963) model, there was a gain in precision of the estimates for the two databases, as well as the modified model, proving the importance in always verifying the form of the Clutter volumetric model that is more adequate and Biological consistent to carry out the projection of the growth and yield of thinned and unthinned eucalyptus plantations.